금강하구 연안에서 고주파 레이더로 관측된 표층해류에 대한 객관적 유속산출 적용 - 황진아; 이상호; 최병주; 김창수; Hwang, Jin-A; Lee, Sang-Ho; Choi, Byung-Joo; Kim, Chang-Soo (Pada (Hanʼguk Haeyang Hakhoe), 2011)
Surface currents were observed by high-frequency (HF) radars off the Keum River estuary from December 2008 to February 2009. The dataset of observed surface currents had data gaps due to the interference of electromagnetic waves and the deteriorating weather conditions. To fill the data gaps an optimal interpolation procedure was developed. The characteristics of spatial correlation in the surface currents off the Keum River estuary were investigated and the spatial data gaps were filled using the optimal interpolation. Then, the temporal and spatial distribution of the interpolated surface currents and the patterns of interpolation error were examined. The correlation coefficients between the surface currents in the coastal region were higher than 0.7 because tidal currents dominate the surface circulation. The sample data covariance matrix (C), spatially averaged covariance matrix with localization ($C^G_{sm}$) and covariance matrix fitted by an exponential function ($C_{ft}$) were used to interpolate the original dataset. The optimal interpolation filled the data gaps and suppressed the spurious data with spikes in the time series of surface current speed so that the variance of the interpolated time series was smaller than that of the original data. When the spatial data coverage was larger (smaller) than 70% of the region, the interpolation error produced by $C^G_{sm}$ ($C_{ft}$) was smaller compared with that by C. 금강하구 연안역에서 고주파 레이더를 사용하여 2008년 12월부터 2009년 2월까지 표층류를 관측하였는데, 관측된 표층류 자료는 전파의 간섭과 기상 상황에 따라 일시적으로 관측이 이루어지지 않는 구역들이 있었다. 관측된 구역의 자료를 보충하기 위하여 최적보간 과정을 개발하여 적용하였다. 금강하구 연안역에서 표층류의 공간적 상관성의 특성을 조사하고 최적보간법을 이용하여 공간적 결측 구역을 보충하였으며, 보간된 표층류의 시공간적 분포와 산출유속 오차 패턴을 조사하였다. 연구해역 표층 순환에서 조류가 우세하므로 연안역 관측 지점들 사이의 표층해류간 상관계수가 0.7 이상이었다. 원 자료를 보간하기 위해 관측 자료공분산(C), 지역화한 공간평균 공분산($C^G_{sm}$), 지수함수를 이용한 맞춤 평균공분산($C_{ft}$)을 사용하였다. 최적보간이 결측 구간을 채우고, 관측 자료의 시계열 중에서 뾰족하게 튀어나온 비정상적인 자료 부분을 억제하였으며, 그 결과 보간한 유속 자료의 분산은 원 자료의 분산보다 작았다. 공간적 자료획득률이 70% 이상(이하)일 때, $C^G_{sm}$ ($C_{ft}$)를 이용하면 C를 이용한 경우에 비해 보간 오차가 상대적으로 작았다.